2020
DOI: 10.37616/2212-5043.1013
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative blood urea nitrogen-to-left ventricular ejection fraction ratio is an independent predictor of long-term major adverse cardiac events in patients undergoing coronary artery bypass grafting surgery

Abstract: Background Long-term mortality rate following coronary artery bypass grafting (CABG) procedure is still considered to be high despite advances in surgical techniques and perioperative management. Identifying high-risk patients by using cost-effective and clinically useful parameters is needed. Methods Patients who were admitted to our cardiology clinic with the diagnosis of coronary artery disease and underwent CABG between January 2008 and August 2010 were included. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Of note, the recent evidence suggested that serum elevation of BUN predicted a worse outcome in patients with acute MI, acute coronary syndrome, and following elective percutaneous coronary procedures (18)(19)(20). Recent work reported that BUN-to-left ventricular ejection fraction (LVEF) ratio independently predicted the incidence of long-term major adverse cardiac events (MACEs) including mortality and newonset decompensated HF in patients undergoing CABG (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the recent evidence suggested that serum elevation of BUN predicted a worse outcome in patients with acute MI, acute coronary syndrome, and following elective percutaneous coronary procedures (18)(19)(20). Recent work reported that BUN-to-left ventricular ejection fraction (LVEF) ratio independently predicted the incidence of long-term major adverse cardiac events (MACEs) including mortality and newonset decompensated HF in patients undergoing CABG (21).…”
Section: Discussionmentioning
confidence: 99%
“…Arnan and his colleagues identified that postoperative BUN was a marker of stroke risk following cardiac surgical procedures (21). Liu et al observed that BUN could predict the in-hospital mortality of patients with acute aortic dissection (AAD) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Dengan demikian, urea darah mungkin mencerminkan disregulasi neurohormonal pada pasien dengan fraksi ejeksi ventrikel kiri (LVEF) yang menurun. 4 Osmolalitas plasma yang terdiri dari kadar glukosa darah, ureum darah, dan natrium yang sebelumnya telah dipelajari dan memiliki nilai yang baik dalam memrediksi prognosis pasien AMI seharusnya dapat memberikan gambaran yang lebih baik untuk prognosis pasien. 5 Fraksi ejeksi ventrikel kiri (LVEF) yang menurun dikaitkan dengan kematian yang lebih besar di antara pasien dengan STEMI.…”
Section: Pendahuluanunclassified
“…Blood urea nitrogen (BUN) is a surrogate of renal dysfunction and was shown to be superior to creatinine for the evaluation of prognosis in AMI patients [10] ; left ventricular ejection fraction (LVEF) is the most commonly used index to re ect the cardiac function [11] . In recently years, a new index, BUN to LVEF ratio (BLR), has been proposed to evaluate the outcome in patients with cardiovascular diseases [12][13][14][15] . However, no studies, to the best of our knowledge, have been explicitly designed to assess the short term prognostic value of BLR in STEMI patients.…”
Section: Introductionmentioning
confidence: 99%